2018
DOI: 10.1364/boe.9.003711
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent epidural needle placement using fiber-probe optical coherence tomography in a piglet model

Abstract: Incorrect needle placement during an epidural block causes medical complications such as dural puncture or spinal cord injury. We propose a system combining an optical coherence tomography imaging probe with an automatic identification algorithm to objectively identify the epidural needle-tip position and thus reduce complications during epidural needle insertion. Eight quantitative features were extracted from each twodimensional optical coherence tomography image during insertion of the needle tip from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…OCT has been integrated with fiber-optic catheters and endoscopes for numerous internal imaging applications 40 43 . Fiber-optic based OCT probe systems have been proposed in epidural anesthesia needle guidance and provided promising results in identifying epidural space in pig models 44 , 45 . In the previous study, our group has also reported a forward-imaging endoscopic OCT needle device for real-time epidural anesthesia placement guidance and demonstrated its feasibility in piglets in vivo 26 .…”
Section: Introductionmentioning
confidence: 99%
“…OCT has been integrated with fiber-optic catheters and endoscopes for numerous internal imaging applications 40 43 . Fiber-optic based OCT probe systems have been proposed in epidural anesthesia needle guidance and provided promising results in identifying epidural space in pig models 44 , 45 . In the previous study, our group has also reported a forward-imaging endoscopic OCT needle device for real-time epidural anesthesia placement guidance and demonstrated its feasibility in piglets in vivo 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we were the first to propose side looking fiber-needle swept-source OCT (SSOCT) imaging for the identification of epidural space with a high success rate 17 and high sensitivity (97.5%), specificity (95%), and accuracy (96.2%). 18 The transversus abdominis fascia plane has not been previously identified in real-time by OCT imaging. In training to perform a TAP block, needle "tip" visualization, in addition to hand-eye coordination and needle visualization, is the most challenging.…”
mentioning
confidence: 97%
“…In our previous studies, we were the first to propose side looking fiber-needle swept-source OCT (SSOCT) imaging for the identification of epidural space with a high success rate 17 and high sensitivity (97.5%), specificity (95%), and accuracy (96.2%). 18…”
mentioning
confidence: 99%